Bridging the Sciences of Mindfulness and Romantic Relationships: A Theoretical Model and Research Agenda. (February 2017) - Karremans, Johan C.; Schellekens, Melanie P. J.; Kappen, Gesa
Research on mindfulness, defined as paying conscious and non-judgmental attention to present-moment experiences, has increased rapidly in the past decade but has focused almost entirely on the benefits of mindfulness for individual well-being. This article considers the role of mindfulness in romantic relationships. Although strong claims have been made about the potentially powerful role of mindfulness in creating better relationships, it is less clear whether, when, and how this may occur. This article integrates the literatures on mindfulness and romantic relationship science, and sketches a theory-driven model and future research agenda to test possible pathways of when and how mindfulness may affect romantic relationship functioning. We review some initial direct and indirect evidence relevant to the proposed model. Finally, we discuss the implications of how studying mindfulness may further our understanding of romantic relationship (dys)functioning, and how mindfulness may be a promising and effective tool in couple interventions.